Structural transformation in the world economy: On the significance of developing countries - Deepak Nayyar (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper outlines the contours of global economic development, since 1980, to analyse underlying factors and consider future implications. The increased economic significance of developing countries, reflected in their share of world output, manufacturing and trade, is striking. But development, driven by rapid economic growth, has been most uneven. It is concentrated in a few economies, the Next-14, which have led the catch-up process. Their similarities - initial conditions, enabling institutions and supportive governments - suggest lessons for latecomers. Their experience shows that there are alternative paths to development, rather than unique solutions, so that one-size-does-not-fit-all and there are choices to be made. And it is clear that inclusive societies alone can sustain rapid growth and transform it into development that improves the wellbeing of their people.
Keywords: 330; global economy; inclusive growth; transformation; development